2019
DOI: 10.1080/21691401.2018.1548473
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin immobilized Fe 3 O 4 magnetic nanoparticles carried with n -butylidenephthalide as targeting-based anticancer agents

Abstract: (2019) Riboflavin immobilized Fe 3 O 4 magnetic nanoparticles carried with n-butylidenephthalide as targeting-based anticancer agents, Artificial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…The utilization of SPIONs is broadly applied as a drug delivery agent or carrier in carcinoma therapeutic purpose. Iron oxide based MNPs were long exercised for different biomedical functions including drug carriers, magnetic hyperthermia, MRI imaging and cancer therapeutic agents in lung cancer [83][84][85][86]. The implication of iron oxide based MNPs has currently been demonstrated by Wang et al, in MRI and ultrasound ablation therapy as shown in Figure 3 [83].…”
Section: Drug Deliverymentioning
confidence: 99%
“…The utilization of SPIONs is broadly applied as a drug delivery agent or carrier in carcinoma therapeutic purpose. Iron oxide based MNPs were long exercised for different biomedical functions including drug carriers, magnetic hyperthermia, MRI imaging and cancer therapeutic agents in lung cancer [83][84][85][86]. The implication of iron oxide based MNPs has currently been demonstrated by Wang et al, in MRI and ultrasound ablation therapy as shown in Figure 3 [83].…”
Section: Drug Deliverymentioning
confidence: 99%
“…The results demonstrated that the as-prepared functional MNPs can be used to effectively target and inhibit the cell growth, have no toxicity toward non-targeted cells, and have the potential to be used as anti-cancer agents. More in vivo tests must be further performed in order to assess the clinical relevance of this approach [87].…”
Section: Drug Deliverymentioning
confidence: 99%
“…The BP‐Fe 3 O 4 @RFMP MNPs did not show any significant adverse effects on non‐target cells. The cell viability was two times lower by the use of Fe 3 O 4 @RFMP MNPs immobilised with BP than by the use of freeform BP at the same concentration [102].…”
Section: Application Of Hybrid Nps Against Different Type Of Cancersmentioning
confidence: 99%